Ground beetles in city forests: does urbanization predict a personality trait? - Schuett, Wiebke; Delfs, Berit; Haller, Richard; Kruber, Sarah; Roolfs, Simone; Timm, Desiree; Willmann, Magdalena; Drees, Claudia (PeerJ, 2018)
Background Urbanization leads to substantial changes in natural habitats with profound effects on wildlife. Understanding behavioural responses to such environmental change is essential for identifying which organisms may adapt, as behaviour is often the first response to altered conditions. Individuals in more urbanized habitats may be expected to be more exploratory and bolder than their conspecifics in less urbanized habitats as they may be better able to cope with novel challenges. Methods In a two-year field study we tested ground beetles from differently urbanized forests for their exploratory behaviour (in a novel environment) and their risk-taking (death-feigning). In total, we tested ca. 3,000 individuals of four forest-dwelling ground beetle species from eight within-city forest patches. In the second year, we also transferred ca. 800 tested individuals of two species to the laboratory to test for consistent behavioural differences (i.e. personality differences) under standardised conditions. Results Individuals were generally more exploratory in more urbanized than in less urbanized areas but only in one year of the study. Exploratory behaviour was not predicted by population density but increased with temperature or showed a temperature optimum. Exploration was consistent over time and individuals that were more exploratory also took higher risks. Discussion We demonstrated that species which are generally less directly exposed to human activities (e.g., most invertebrates) show behavioural responses to urbanization. Effects of urbanization were year-dependent, suggesting that other environmental conditions interacted with effects of urbanization on beetle behaviour. Furthermore, our results indicate that different personality compositions might cause behavioural differences among populations living in differently urbanized habitats.
Keywords: Anthropogenic change; Boldness; Carabid; Density; Environmental driver; Exploration; Invertebrate; Novel environment; Open field; Temperature